Interdependence: The Pathway to the Inclusion of People with Intellectual Disabilities and Immigrant Disability Support Workers - Neri, Deanna Joyce (Anthropologica, 2022)
Friendship and social connections generally improve quality of life and well-being. However, research shows that people with intellectual disabilities face challenges forming and maintaining friendships. Disability support workers play an indispensable yet under-recognized role in developing friendships with people with intellectual disabilities. Because disability support workers are disproportionately immigrant women, as they facilitate the inclusion of their clients, they too experience social isolation. After conducting in-depth interviews with disability support workers living in Edmonton, Canada, for my master’s thesis project, I offer the following observations. First, staff and clients became friends with one another in part due to weak family ties and limited social networks. Second, relationships that felt genuine helped staff better understand their clients and gave the staff a deeper sense of purpose in life. Third, the context, environment, and frequency of meetings were essential for the development of friendships. Fourth, friendships among people both with and without disabilities were crucial for community development. Overall, based on these interviews I suggest that genuine friendships between people with intellectual disabilities and care workers can help foster a sense of belonging and are integral to community- building. My research also suggests that the meaning of friendship ought to be expanded beyond current understandings.